Producing Radio Programs, Mainstreaming Gender Equity: A Case Study of Radio Sonora Semarang - Agus Triyono; Arni Ernawati (Jurnal Komunikasi Islam, 2022)
There has been an increase in discussion about gender mainstreaming-related issues on media. Mass media producers’ awareness about gender equity has remained questionable, even regarded as not presenting gender equity as expected. This study attempts to focus on how the production of news programs in Radio Sonora Semarang regarding the issue of gender equality, particularly to what extent the role of women in the process of radio program production. Using a qualitative approach and conducting interviews with Radio Sonora's journalists and the production program team, the findings have revealed that Radio Sonora Semarang highly upholds the values of gender equality in the production process of its programs. There has been mutual respect amongst media workers both men and women in the radio Sonora during program production process. Indeed, women can take roles equally to men without leaving their nature as women.